2015
DOI: 10.1088/0004-6256/149/3/107
|View full text |Cite
|
Sign up to set email alerts
|

THEGRISM LENS-AMPLIFIED SURVEY FROM SPACE(GLASS). II. GAS-PHASE METALLICITY AND RADIAL GRADIENTS IN AN INTERACTING SYSTEM ATZ≃ 2

Abstract: We present spatially resolved gas-phase metallicity for a system of three galaxies at z = 1.85 detected in the Grism Lensed-Amplified Survey from Space (GLASS). The combination of HST's diffraction limit and strong gravitational lensing by the cluster MACS J0717+3745 results in a spatial resolution of 200 − 300 pc, enabling good spatial sampling despite the intrinsically small galaxy sizes. The galaxies in this system are separated by 50 − 200 kpc in projection and are likely in an early stage of interaction, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 83 publications
3
80
0
1
Order By: Relevance
“…The available observations of HII regions for high-z galaxies do not allow the formation of a robust conclusion on the evolution of the metallicity gradients (e.g. Yuan et al 2011;Queyrel et al 2012;Stott et al 2014;Jones et al 2015). In fact, high-redshift observations show a complex situation with gas-phase components showing a variety of metallicity gradients that could respond to the action of different physical processes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The available observations of HII regions for high-z galaxies do not allow the formation of a robust conclusion on the evolution of the metallicity gradients (e.g. Yuan et al 2011;Queyrel et al 2012;Stott et al 2014;Jones et al 2015). In fact, high-redshift observations show a complex situation with gas-phase components showing a variety of metallicity gradients that could respond to the action of different physical processes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As gas is converted into stars, metallicity increases at a rate modulated by the degree of mass loss. Right: Metallicity as a function of stellar mass for galaxies at z 2, from Jones et al [75]. Blue triangles are from composites of non-lensed galaxies demonstrating a steep mass-metallicity relation especially at masses below 10 9 M .…”
Section: Pos(bash2015)013mentioning
confidence: 99%
“…To date several measurements have been made for gravitationally lensed galaxies which provide the most reliable results due to their high spatial resolution [75,79,80]. A growing number of non-lensed galaxies also have limited spatially resolved metallicity measurements which show interesting trends with global demographic properties [81].…”
Section: Pos(bash2015)013mentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we test the effect of an additional starburst contribution to galaxy star formation histories that complete observations of the star-forming main sequence may not reflect but may, nevertheless, be necessary to explain the density profiles of dwarf systems (e.g., Weisz et al 2012;Amorisco et al 2014;Madau et al 2014) and observed in a lensed dwarf systems at high redshift (Jones et al 2014). Such bursts would represent an further random process that produces spikes in the star formation rate, perhaps as some tidal event funnels gas into the central regions of the galaxy.…”
Section: Appendix B: Additional Starburstsmentioning
confidence: 99%